2009
DOI: 10.1111/j.1365-2133.2009.09485.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of skin protection measures in prevention of occupational hand eczema: results of a prospective randomized controlled trial over a follow-up period of 1 year

Abstract: The generally recommended skin protection regimen seems to provide effective prevention of occupational skin disease. Therefore, the compliance to follow the skin protection regimen, especially the use of skin protection, should be enhanced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 28 publications
1
62
0
3
Order By: Relevance
“…Based on the HEROS results, significant differences between smokers and nonsmokers were observed only for erythema and vesicles (table 2). These results were not influenced by the intervention of the aforementioned study [32], and there was no association between smoking status and intervention effect. At the 1-year follow-up, only 3 subjects, 2 of them smokers, reported that they had been unable to work in the past year and a total of 13 subjects reported current topical application of steroids on both hands.…”
Section: Resultsmentioning
confidence: 49%
See 2 more Smart Citations
“…Based on the HEROS results, significant differences between smokers and nonsmokers were observed only for erythema and vesicles (table 2). These results were not influenced by the intervention of the aforementioned study [32], and there was no association between smoking status and intervention effect. At the 1-year follow-up, only 3 subjects, 2 of them smokers, reported that they had been unable to work in the past year and a total of 13 subjects reported current topical application of steroids on both hands.…”
Section: Resultsmentioning
confidence: 49%
“…All participants gave their informed consent to take part in a standardized interview and a dermatological examination of their hands. A subgroup of 1,020 male metal workers (406 smokers and 614 nonsmokers) which fulfilled our inclusion criteria for a recently published intervention study [32] gave their written informed consent to be followed-up for 1 year. The study design was approved by the local ethics committee of the University of Erlangen-Nuremberg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that the skin protection programme (using BCs and skin care creams) is effective as well as the use of BCs alone, contrary to moisturizers alone, but the best protective effect was obtained by combining BCs and moisturizers. Kütting et al [59] underline the contrast with the results of an Austrian prospective 4-armed randomized controlled trial on 485 of 1,006 workers coming from building (n = 198) and timber (n = 287) industries, followed over 1 year, in which each subject was assessed by clinical hand dermatitis categorization, transepidermal water loss and subjective perception. None of the 4 groups showed a protective effect on dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…A signifi cant deterioration was found in the control group. Therefore, the compliance to follow the skin protection regimen, especially the use of skin protection creams, should be enhanced [ 96 ].…”
Section: Moisturizers: Field and Patient Studiesmentioning
confidence: 99%